2014
DOI: 10.1016/j.egypro.2014.11.751
|View full text |Cite
|
Sign up to set email alerts
|

Can We Treat CO2 Well Blowouts like Routine Plumbing Problems? A Study of the Incidence, Impact, and Perception of Loss of Well Control

Abstract: Risk communication literature suggests that for a number of reasons, the public may perceive a risk to be greater than indicated by its statistical probability. Public concern over risk can lead to significant and costly delays in project permitting and operations. Considering these theories, media coverage of CO 2 -related well blowouts in 2013 gave rise to the questions: What is the risk of CO 2 well blowouts associated with CCUS through CO 2 EOR? What is the potential public perception of those risks? What … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…An important example is the characterization, remediation, and surveillance of performance of the many wells in a typical EOR system. Reporting of these data to regulatory authorities is typically inadequate to support a monitoring programme (Gan and Frohlich, 2013;Porse et al, 2014). It is important to implement a protocol to make data from the operator's confidential records available for the monitoring programme.…”
Section: Ccus Projects and Monitoringmentioning
confidence: 99%
“…An important example is the characterization, remediation, and surveillance of performance of the many wells in a typical EOR system. Reporting of these data to regulatory authorities is typically inadequate to support a monitoring programme (Gan and Frohlich, 2013;Porse et al, 2014). It is important to implement a protocol to make data from the operator's confidential records available for the monitoring programme.…”
Section: Ccus Projects and Monitoringmentioning
confidence: 99%
“…Statistics of onshore well blowout incidents and associated risk perception, including blowouts from steam injection wells, have been analyzed as a way of inferring blowout risk for a future widespread implementation of onshore GCS. 11,12 Maps of near-offshore oil and gas fields in the Gulf of Mexico and elsewhere show very high densities of old wells subject to potential individual and collective leakage including blowouts. 13 As part of evaluating the GCS potential of the offshore Gulf of Mexico region, it is necessary to evaluate the consequences of potential major CO 2 well blowouts.…”
Section: Prior Workmentioning
confidence: 99%
“…Duncan et al (2009) studied the 35-year history of CO 2 -EOR in the United States (at the time) and suggested that the probability of leakage was very low. Leakage of CO 2 through old boreholes has occurred in relation to EOR projects in the United States, 3 but Porse et al (2014) suggest that the perceived risk of CO 2 well blowouts in EOR operations is greater than the technical risk. Kü hn et al (2013) tested 12 legacy boreholes for a possible enhanced gas recovery project in the depleted Altmark natural gas field in Germany, and the authors found that these existing wells would still maintain integrity after injecting 100,000 t of CO 2 .…”
Section: Risk Scenario Cmentioning
confidence: 99%